Case Report: preoperative prediction of aneurysm rupture site using aortic morphological and biomechanical analysis validated by intraoperative imaging - Tianming Huang; Tianming Huang; Yifeng Pan; Yifeng Pan; Shuangxiang Lin; Yuanming Luo; Bing Chen; Bing Chen (Frontiers in Cardiovascular Medicine)
Prediction of aneurysm rupture has been a great challenge for decades. We report a successful rupture site prediction on a 97 mm abdominal aortic aneurysm (AAA). A 73-year-old man with an 11-year history of AAA presented to our outpatient clinic with a one-week history of hemoptysis. After undergoing multidimensional dynamic CTA imaging, the high rupture risk region was predicted through comprehensively inspecting the image-derived characteristics of biomechanics, morphology, and intraluminal thrombus distribution. Owing to financial difficulties, the patient declined treatment. The patient returned to the hospital 140 days later with severe acute abdominal pain. Follow-up CT imaging revealed contrast extravasation accompanied by a large retroperitoneal hematoma, indicating active aneurysmal rupture. Emergency endovascular aneurysm repair (EVAR) was subsequently performed. Notably, the rupture site corresponded to the region previously predicted by our biomechanical analysis and was confirmed intraoperatively via digital subtraction angiography. The patient's postoperative course was uneventful, and he remained in stable condition at the 3-month follow-up. This successful prediction serves as a starting point for verifying the considerations regarding aneurysm rupture mechanism, which would benefits innovative treatment options in future.